A new looped tether transportation system with multiple rungs. (December 2021) - Wang, Qingtao; Wen, Hao; Li, Gangqiang; Zhu, Zheng H.; Zhang, Zhiyong
Abstract: A novel concept of a looped tether transportation system with multiple rungs (L-TTS-R) is proposed for highly efficient payload transfer in space. In addition to two huge platforms connected by two parallel tethers with multiple moving climbers, some rigid rungs are evenly distributed between the two tethers in L-TTS-R to suppress the libration movement of the system and to reduce or avoid the risk of collision between climbers and tethers in the process of payload transportation. To establish an accurate model of L-TTS-R in the framework of multibody system dynamics, the gradient deficient beam elements of the absolute nodal coordinate formulation (ANCF) are used to mesh two tethers. The sliding joint based on ANCF is introduced to build up the contact interaction model between tethers and climbers. The generalized forces acting on the L-TTS-R, for example, the gravitational force and the elastic force, are derived in brief. The generalized-alpha method is used to solve the dynamics equations of the constrained flexible multibody systems. Some representative examples are given to validate the effectiveness of the proposed L-TTS-R model for space payload transfer missions and to assess the influence of rungs on the system libration suppression, the climber collision risk avoidance, the relative oscillation and pitching motion of platforms, and the tether tensions. The numerical results reveal that the L-TTS-R shows distinct effects on suppressing the overall libration of the system, reducing or even avoiding the risk of collision between climbers and tethers and decreasing significantly the oscillating magnitudes of the relative distances between two platforms, and these effects are more visible with increasing the number of rungs. Highlights: A novel concept of a looped tether transportation system with multiple rungs (L-TTS-R) is proposed. The absolute nodal coordinate formulation based beam element and sliding joint are used to establish the model of L-TTS-R. The influence of rungs on the system dynamics is assessed.